Children’s Voices on the COVID-19 Pandemic as Presented in Swedish Junior and Daily Newspapers - Stjernswärd, Sigrid; Meier, Marie; Tilgmann, Carola; Glasdam, Stinne (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
This study focuses on children’s voices as they were presented in Swedish newspapers during the COVID-19 pandemic. It explores the ways in which journalists featured children’s experiences of everyday life during a time of crisis. A descriptive, thematic text analysis of 83 articles resulted in four prominent themes: children’s voices as a mouthpiece for or against school closure, children as cocreators of a new normal daily life, children as responsible and caring citizens, and COVID-19 as a magnifying glass for existing vulnerabilities in everyday life. The selection and representation of children’s viewpoints was adult led and limited, and the study thus calls for further research on media constructions of children/childhood and related consequences.